(untitled) (Integral Research, 2025)
Bilingualism is a natural phenomenon in migrants’ communities. The 0000-0003-4237-246X -French minority group in Abidjan are regularly plagued with the problem of identity which is reflected in their language use and naming patterns. Previous studies on migrants’ settlements have focused mostly on language shift leading to language endangerment. This study examines patterns of naming among the Yorùbá in Abidjan which has received little attention from scholars. The study employs a descriptive survey methodology to investigate patterns of naming among the Yorùbá migrants. The theoretical framework for this study are social identity and accommodation theories. The study reveals three different types of names among the migrants: some write their names according to Yorùbá spellings, some spellings are usually patterned after French spellings rather than Yorùbá and the third are those who give their children francophone names instead of names that will reflect their Yorùbá ancestry, The desire for identity among their francophone neighbours has impacted negatively on language use and naming practices of the Yorùbá migrants who have settled among the Ivorians. It is believed that this practice promotes accommodation and access to certain benefits as citizens. However, the attitude of the Yorùbá migrants to the Yorùbá language is positive as many among the older generation claim they love the language and employ it in inter-personal communication. The study concludes that although the naming pattern demonstrates integration to the new environment, it threatens the continued survival of the Yorùbá language and culture in Abidjan. The paper calls for linguistic and cultural revival among the people especially as naming reflects both linguistic and cultural background.